Puerarin action on stem cell proliferation, differentiation and apoptosis: therapeutic implications for geriatric diseases - Ma, Ruishuang; Zhao, Lucy; Zhao, Yuming; Li, Yue (Phytomedicine, 2022)
Background - Aging is associated with a decline in cognitive and physical functions and various geriatric diseases, such as cardiovascular and neurodegenerative diseases. Puerarin (Pue), one of the main active flavonoids of Radix Puerariae (R. pueraria), is reportedly effective in treating geriatric diseases, including cardiovascular disease and hypertension. - Purpose - This review aims to summarize and discuss the profound physiological impact of Pue on various stem cell populations and provide new insights into the use of Pue for the prevention and treatment of geriatric diseases. - Methods - The literature was retrieved from the core collection of electronic databases, such as Web of Science, Google Scholar, PubMed, and Science Direct, using the following keywords and terms: Puerarin, Stem Cell, Proliferation, Differentiation, Apoptosis, and Geriatric diseases. These keywords were used in multiple overlapping combinations. - Results - Pue is effective in the treatment and management of age-related diseases, such as cardiovascular disease, diabetes, hypertension, and cerebrovascular disease. Pue exerts significant physiological effects on various stem cell populations, including their self-renewal/proliferation, differentiation and apoptosis. Most importantly, it could improve the efficiency and accuracy of stem cell therapy for treating various geriatric diseases. Further studies are essential to improve our understanding of the underlying mechanisms and elucidate their significance for future clinical applications. - Conclusion - The effects of Pue on various stem cell populations and their regulatory mechanisms are discussed in detail to provide new insights into the use of Pue in the prevention and treatment of geriatric diseases.
Available online 29 December 2021
Gesehen am 20.06.2022